The role of workday characteristics on perceived stress and time pressure among nurses in Finnish long-term care - a cross-sectional study - Visa Väisänen; Salla Ruotsalainen; Laura Hietapakka; Juhani Sulander; Timo Sinervo (BMC, 2024)
Abstract Background Aging populations and nursing workforce issues are causing challenges for long-term care globally, and therefore, improving the work-related wellbeing and retention of nurses is crucial. As such, gaining a further understanding of the factors that affect work strain in long-term care is important. Previously, the effect of job demands on the wellbeing of nurses has been researched principally by subjective instruments. In this study, we examined the relationship between indirectly measured workday characteristics and perceived stress and time pressure among nurses working in Finnish long-term care (assisted living facilities with 24-hour assistance). Methods A total of 503 nurses from 44 assisted living facilities across Finland completed time measurement surveys and wellbeing questionnaires. The data were linked with client characteristics from the Resident Assessment Instrument register. The relationships between the measured number of care events during the workday, clients' care needs, and the amount of breaktime and perceived stress and time pressure were analyzed using multivariate logistic regression. Results Nurses who had more care events and clients with greater care needs were at higher odds of having high stress. More care events and reduced breaktime were associated with high time pressure. Disruptions during the workday were strongly associated with both high stress and time pressure. Last, nurses who were under high stress and time pressure worked more often in teams with lower team autonomy. Conclusions Our findings on indirectly measured job demands indicate that dividing the workload equally among nurses through better work division can help reduce the stress and time pressure of nurses in long-term care. In addition, ensuring sufficient breaktime and preventing unnecessary disruptions is important. To help recruit and retain the care workforce, fair management of work that accounts for varying client care needs and workload is needed. In addition, legislative and governance tools, such as staffing level regulation, and further consideration of job demands might aid in reducing the job strain of nurses. Patient or public contribution Patients or nurses were not involved in the design of the study, analysis, or interpretation of the results, or in the preparation of the manuscript.